Dzieje pojęcia a historia gniazda słowotwórczego – preliminaria (na przykładzie pojęcia DEMOKRACJA) - Pastuch, Magdalena (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2025)
The article explores how the concept of democracy has evolved throughout the history of the Polish language. The linguistic material is drawn from both dictionaries and language corpora. The author employs a combination of two approaches: one based on word formation – specifically, the wordformation nest method – and the other rooted in historical semantics. This methodological combination has proven effective, revealing a connection between the development of the word-formation nest and the evolution of the concept of democracy. Moreover, it enabled the author to identify a relationship between the degree of stabilization of loanwords and the size of their respective word-formation nests. The study of the Polish concept of democracy allowed the author to answer the detailed research question posed in the article. The conclusions are as follows: a) the centre of the word-formation nest overlaps with the centre of the semantic field; b) the structure of the word-formation nest reflects the variability of the concept; c) the history of the main (top) word in the word-formation nest influences the axiology of the concept; d) the growth of the word-formation nest correlates with the stabilization of the loanword.